2017
DOI: 10.1037/dev0000209
|View full text |Cite
|
Sign up to set email alerts
|

Reading self-perceived ability, enjoyment and achievement: A genetically informative study of their reciprocal links over time.

Abstract: Extant literature has established a consistent association between aspects of reading motivation, such as enjoyment and self-perceived ability, and reading achievement, in that more motivated readers are generally more skilled readers. However, the developmental etiology of this relation is yet to be investigated. The present study explores the development of the motivation–achievement association and its genetic and environmental underpinnings. Applying cross-lagged design in a sample of 13,825 twins, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 70 publications
5
62
0
Order By: Relevance
“…They reported slightly different results for the eighth grade with reading achievement weakly correlated with enjoyment of reading, r = .22; and moderately correlated with reading self-efficacy, r = .35 and socio-economic status, r = .32. Similar gender and age effects on enjoyment of reading are supported by relatively recent studies such as Brozo et al (2014), Guthrie and Wigfield (2000), Hochweber and Vieluf (2018), Malanchini et al (2017) and Loveless (2015).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…They reported slightly different results for the eighth grade with reading achievement weakly correlated with enjoyment of reading, r = .22; and moderately correlated with reading self-efficacy, r = .35 and socio-economic status, r = .32. Similar gender and age effects on enjoyment of reading are supported by relatively recent studies such as Brozo et al (2014), Guthrie and Wigfield (2000), Hochweber and Vieluf (2018), Malanchini et al (2017) and Loveless (2015).…”
supporting
confidence: 74%
“…Several past studies have investigated and reported the link between enjoyment of reading and reading achievement (Clark & Douglas, 2011;Froiland & Oros, 2014;Howie et al, 2017;Malanchini et al, 2017;Wang & Guthrie, 2004). It has been proposed that enjoyment of reading is associated with cognition and comprehension, is an indicator of reading interest and reading involvement and is a component of intrinsic motivation which can affect reading achievement (Brozo et al, 2014;Chapman & Tunmer, 1995;Guthrie et al, 2007;Schiefele, Schaffner, Möller, & Wigfield, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, statistical separation of NonCog from Cog, although artificial, allows us to test if heritable traits other than cognitive ability influence educational attainment and to explore what those traits may be. Our finding that NonCog genetics account for roughly half of all genetic variance in EA should motivate future longitudinal studies to collect repeated measures of cognitive and non-cognitive skills in order to study their reciprocal relationship across development 83,84 .…”
Section: Finally Biological Annotation Analyses Suggest Similaritiesmentioning
confidence: 95%